The Relationship between Knowledge Level, Attitude, and Source of Information Maternal with Pentavalent Immunization Completeness - Lisencia, Elissa Dewi; Hadiwiardjo, Yanti Harjono; Masroekin, Mashoedojo Pratonodihardjo (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2018)
Background: Pentavalent immunization was developed by the Strategic Advisory Group of Experts on Immunization (SAGE) by adding Hib vaccine and combined it into one single preparation. The advantage of using the pentavalent vaccine is the protection of five diseases, easy to use and reducing drop out numbers. The aim of this study was to determine the relation of mothers knowledge, attitude, and information source with pentavalent immunizations completeness in Cipondoh Primary Health Care. Method: This was an analytical non-paired comparative study with cross-sectional design by consecutive sampling technique. There were 105 respondents. The samples were mothers who have minimal 6 months old baby in Cipondoh Primary Health Care work area. Data were collected using questionnaires. Results: The results of bivariate test using chi-square shows there was a relation between mothers knowledge and pentavalent immunizations completeness (p-value=0.001; OR=6.1; CI=2.1-17.2), mothers attitude and pentavalent immunizations completeness (p-value=0.027; OR=3.5; CI=1.1-11.3), mothers information source and pentavalent immunizations completeness (p-value=0.011; OR=4.4; CI=1.5-12.4). Conclusion: There was a relationship between maternal knowledge level, maternal attitude, information source and pentavalent immunizations completeness.